Impact of macroeconomic variables and digital technology on economic growth in ASEAN-5 countries - Fito Ardianto Putra; Firdha Aksari Anindyntha (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This research aims to examine and analyze the impact of foreign direct investment (FDI), internet users, interest rates, and inflation on economic growth in the five founding ASEAN countries: Indonesia, Malaysia, Singapore, the Philippines, and Thailand.Method — This research employs a quantitative approach using panel regression analysis to identify and measure the impact of macroeconomic variables and digital technology on economic growth in the five founding countries of ASEAN. The data, spanning the period from 2005 to 2022, is sourced from the World Bank and other relevant international databases.Result — The research results indicate that foreign direct investment (FDI), internet users, and interest rates significantly influence economic growth in ASEAN countries. Conversely, inflation has a negative but insignificant effect on economic growth in the region. These findings underscore the importance of FDI, digital technology adoption, and effective interest rate management in driving economic growth. The insignificant impact of inflation suggests that it may not play a major role in the economic growth dynamics of the ASEAN-5.Practical implications — The research has practical implications for ASEAN stakeholders. Governments can attract FDI and promote digital infrastructure to foster economic growth. Investors can target sectors that benefit from FDI and digital technology. Central banks can adjust interest rates to stimulate growth while managing inflation. Businesses can prioritize digital transformation for development. Collaboration among ASEAN states can further enhance regional growth. Aligning strategies with these findings can boost ASEAN's prosperity and competitiveness.